The green synthesis of silver nanoparticles from Morinda citrifolia root extract and its methylene blue degradation - Mat Hussin, Zurhana; Mohamad Jufly, Fairuza Husna; Yusof, Nurul Syuhada; Daud, Shaari (GADING Journal of Science and Technology, 2024)
This study evaluates the effects of ethanol and hot water extracts of Morinda citrifolia (M. citrifolia) root on the green synthesis of silver nanoparticles (MCAgNPs) for the photocatalytic degradation of methylene blue (MB). The MCAgNPs formation was confirmed by the UV-Vis spectroscopy. The synthesised silver nanoparticles in solution have shown maximum absorptions at 419 nm for MCEN and 429 nm for MHWN spectrophotometrically. The FTIR result showed that effective functional molecules such as hydroxyl, carboxylic, phenol, and amine groups are responsible for the formation of the nanoparticles. The photocatalytic activity of the synthesised silver nanoparticles was investigated by MB degradation under the sunlight. The synthesised MCAgNPs from ethanol extract (MCEN) was the most effective as it degraded the dye 92.6% at irradiation time of 360 min. The synthesised silver nanoparticles from ethanol M. Citrifolia root extracts exhibit excellent photocatalytic activity against MB molecules and can be potentially applied in water treatment systems.